Implementation and Reinforcement of Student Character Education in Palembang City - Mardiah Astuti; Fajri Ismail; Padjrin Padjrin (STAI Hubbulwathan Duri, 2021)
The study aimed to analyze the inculcation of student character values in schools in Palembang City. The study used a quantitative descriptive method. The data collection used observation, questionnaires, and documentation. The sample of the research was 66 samples with quota sampling technique. The study found that the lack of exemplary reinforcement and habituation decreased the understanding and reflection of students' behavioral character values. Furthermore, learning about character values was integrated through the subjects of Civics and Islamic Religious Education. While the school gave the exemplary family and community reinforcement in the form of regulations, policies, and cooperation between schools, families, and communities regularly, as well as habituation of living with character in daily life was still not optimal. It needed to be optimized again so that the character values in students were closely and maximally attached to students both from speech and action.